Effect of irrigation and nitrogen management practices on productivity and nutrient uptake of direct-seeded rice (Oryza sativa) - SEPAT, SEEMA; KUMAWAT, ANITA (The Indian Journal of Agricultural Sciences, 2020)
An experiment was conducted at ICAR-Indian Agricultural Research Institute, New Delhi during kharif seasons of 2015 and 2016 to evaluate the effect of irrigation and nitrogen management on productivity and profitability in direct-seeded rice. Results showed that an increase in water stress from 20 kPa to 40/10 kPa resulted in the decline of grain yield over the years. Irrigation at 0 and 10 kPa recorded higher grain (4.8 and 4.7 t/ha, respectively) and net returns (45.2 and 46.2 ₹ × 103 /ha, respectively). Similarly, N uptake in grain and total was recorded higher with 0 kPa and 10 kPa, and reduced with increase in water stress at 40/10 kPa. In 2015 and 2016, split N application enhanced the grain yield (5.42 t/ha) than no N application (2.72 t/ha). Change in N application from three to four splits resulted in higher grain yield and net benefit as compared to no N application. Four N splits registered an increase of 6.67% in grain yield compared to three N splits. N splits registered an increase of N uptake in grain and total by 18.14 and 16.26 %, respectively than three N splits (68.9 and 131.2 kg/ha, respectively). Results implied that irrigation at 10 kPa with four N split increased the productivity and profitability of direct-seeded rice.